2005
DOI: 10.1007/s00395-005-0549-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fatty acid metabolism is preserved in the compensated hypertrophic rat heart

Abstract: Cardiac hypertrophy and failure are associated with alterations in cardiac substrate metabolism. It remains to be established, however, whether genomically driven changes in cardiac glucose and fatty acid (FA) metabolism represent a key event of the hypertrophic remodeling process. Accordingly, we investigated metabolic gene expression and substrate metabolism during compensatory hypertrophy, in relation to other cardiac remodeling processes. Thereto, cardiac hypertrophy was induced in rats by supra-renal aort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…40, 41 In rats with compensated cardiac hypertrophy generated by abdominal aortic constriction, cardiac glycolysis was increased without glucose oxidation. 42 In a rat model of LV pressure overload, glucose oxidation was initially increased during the compensated phase of cardiac hypertrophy and then declined in the decompensated phase of HF. 14 In a murine model of LV pressure overload, glucose oxidation, glycolysis, and lactate oxidation were reduced at 6 weeks after the surgery.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%
“…40, 41 In rats with compensated cardiac hypertrophy generated by abdominal aortic constriction, cardiac glycolysis was increased without glucose oxidation. 42 In a rat model of LV pressure overload, glucose oxidation was initially increased during the compensated phase of cardiac hypertrophy and then declined in the decompensated phase of HF. 14 In a murine model of LV pressure overload, glucose oxidation, glycolysis, and lactate oxidation were reduced at 6 weeks after the surgery.…”
Section: Metabolites Of Glycolysis and The Tca Cyclementioning
confidence: 99%
“…33 In addition, several studies have reported normal FA uptake, metabolism and carnitine palmitoyltransferase 1 activity, the rate limiting enzyme in mitochondrial beta-oxidation, in cardiac hypertrophy. 30,32 Our findings suggest that the cardiac hypertrophy caused by loss of Cav1 gene expression in cardiac fibroblasts was not severe enough to trigger a switch in myocardial energy metabolism commonly observed in pressure-or volume-overload induced hypertrophy and heart failure. Additional studies are needed to assess cardiac energy substrate utilization in decompensated and failing Cav1ko hearts.…”
Section: Discussionmentioning
confidence: 85%
“…29 However, recent studies by several groups argue that overt changes in cardiac energy metabolism may depend upon the degree of hypertrophy. [30][31][32] Miyamoto et al, measured the expression of several enzymes involved in FA metabolism and found that the levels of PPARα, a key transcriptional regulator of metabolic genes were normal in volume-overloaded hypertrophied rabbit hearts. 33 In addition, several studies have reported normal FA uptake, metabolism and carnitine palmitoyltransferase 1 activity, the rate limiting enzyme in mitochondrial beta-oxidation, in cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of key genes known to regulate substrate metabolism was unchanged despite decreased left ventricular contractile function. Several studies suggest that the severity of pathological cardiac hypertrophy and heart failure dictates the metabolic switch toward glucose and away from FA as the primary fuel source (13). Our model of cardiac hypertrophy is unique in that the cardiomyopathy does not appear to result in altered cardiac substrate metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…We previous reported the hyperactivation of ERK1/2 in Cav3KO hearts; however, the resulting increase in myocyte cell number and size did not alter myocardial energy metabolism in our model. Several recent studies suggest that overt changes in cardiac energy metabolism may depend upon the degree of hypertrophy (13). As compensatory hypertrophy progresses toward decompensated hypertrophy and eventually heart failure, changes in gene expression become more pronounced resulting in a shift away from FA as a fuel source (1).…”
Section: Discussionmentioning
confidence: 99%